Amyloidosis and Unexpected Death: A Review of Seven Cases. Issue 3 (September 2016) - Presnell, Susan E.; Schandl, Cynthia A.
Amyloidosis, deposition of improperly folded insoluble proteins, may affect one organ or may be systemic. Although plasma cell dyscrasia is frequently implicated in etiology and is due to immunoglobulin light chain production (AL amyloidosis), age-related amyloidosis is believed to be secondary to transthyretin production (ATTR), chronic inflammation-related amyloidosis is thought due to acute phase reactants (AA amyloidosis), and dozens of others are also described. Clinical presentation is dependent upon the organ(s) involved and those associated with unexpected death are expected to involve the cardiovascular system. All cases received for forensic postmortem examination at the Medical University of South Carolina from 2008 to May 15, 2015 were searched to identify any in which amyloidosis was listed as a final diagnosis. Seven cases were identified that met the criteria and were reviewed for demographic information, presentation, cause and manner of death, and assessment of pertinence of the diagnosis of amyloidosis to the cause and manner of death. Interestingly, gross examination of the heart was suggestive of amyloidosis or other infiltrative process in only two of the cases reviewed and a history of myeloma was only noted in one individual. Common gross and microscopic findings are described and relevant medical history and toxicology findings are compared.